Business process re-engineering to digitalise quality control checks for reducing physical waste and resource use in a food company - Garcia-Garcia, Guillermo; Coulthard, Guy; Jagtap, Sandeep; Afy-Shararah, Mohamed; Patsavellas, John; Salonitis, Konstantinos (MDPI, 2021)
Quality control is an essential element of manufacturing operations that reduces product defects and provides excellent products of the right specifications to the end consumer. Industry 4.0 solutions, such as digitalisation, along with lean manufacturing tools, may support quality control operations. This paper presents a case study of a food company wherein quality control checks were optimised using business process re-engineering to reduce physical waste and resource usage. Following close analysis of the company’s pack-house operations, it was proposed to adopt elements of Industry 4.0 by digitalising the quality control process. Implementing such a solution led to a reduction in the time needed to complete recorded checks, an increase in the time the pack-house quality control team spends with packers on the production lines, and the facilitation of defects identification. It also ensured that the product met the customers’ specifications and reduced the likelihood of rejection at the customers’ depot. The new system also enabled monitoring of each line in real-time and gathering of additional information faster and more accurately. This article proves how employing lean principles in combination with Industry 4.0 technologies can lead to savings in resources and a reduction in waste, which leads to improvements in operational efficiency.
Keywords: waste; digitalisation; business process re-engineering; food manufacturing; lean; packing; real-time monitoring; Quality 4.0; Industry 4.0